Nitric oxide synthase isoforms and the effect of their inhibition on meiotic maturation of porcine oocytes - Chmelíková, Eva; Jeseta, Michal; Sedmíková, Markéta; Petr, Jaroslav; Tůmová, Lenka; Kott, Tomás; Lipovová, Petra; Jílek, Frantisek (Zygote (Cambridge, England), 2010)
In this paper we assessed: (i) the change in nitric oxide synthase (NOS) isoforms' expression and intracellular localization and in NOS mRNA in porcine oocytes during meiotic maturation; (ii) the effect of NOS inhibition by N(omega)-nitro-l-arginine methyl ester (l-NAME) and aminoguanidine (AG) on meiotic maturation of cumulus-oocyte complexes (COC) as well as denuded oocytes (DO); and (iii) nitric oxide (NO) formation in COC. All three NOS isoforms (eNOS, iNOS and nNOS) and NOS mRNA (eNOS mRNA, iNOS mRNA and nNOS mRNA) were found in both porcine oocytes and their cumulus cells except for nNOS mRNA, which was not detected in the cumulus cells. NOS isoforms differed in their intracellular localization in the oocyte: while iNOS protein was dispersed in the oocyte cytoplasm, nNOS was localized in the oocyte cytoplasm and in germinal vesicles (GV) and eNOS was present in dots in the cytoplasm, GV and was associated with meiotic spindles. l-NAME inhibitor significantly suppressed metaphase (M)I to MII transition (5.0 mM experimental group: 34.9% MI, control group: 9.5% MI) and at the highest concentration (10.0 mM) also affected GV breakdown (GVBD); in contrast also AG inhibited primarily GVBD. The majority of the oocytes (10.0 mM experimental group: 60.8%, control group: 1.2%) was not able to resume meiosis. AG significantly inhibited GVBD in DO, but l-NAME had no significant effect on the GVBD of these cells. During meiotic maturation, NO is formed in COC and the NO formed by cumulus cells is necessary for the process of GVBD.
Keywords: Protein Isoforms; meióza; Meiosis; Female; Nitric Oxide Synthase; synthasa oxidu dusnatého; Cumulus Cells; ženské pohlaví; protein - isoformy; NG-nitroargininmethylester; Microscopy, Confocal; oocyty; messenger RNA; Oocytes; Animals; zvířata; kumulární buňky; konfokální mikroskopie; NG-Nitroarginine Methyl Ester; RNA, Messenger